Symptoms Experience among People Living with Human Immunodeficiency Virus in a Clinic - Gautam, Roshani (Journal of Nursing Education of Nepal, 2022)
Introduction: Symptoms assessment is the foremost and first step of health care management. People  living with Human Immunodeficiency Virus (HIV) experience various physical and psychological  symptoms throughout the disease. Adherence to antiretroviral therapy (ART) and an individual’s  quality of life is adversely affected by poorly managed severe symptoms. This study aimed to assess  the prevalence of symptoms among people living with HIV who attended an Antiretroviral Therapy  (ART) clinic. Methods: A descriptive cross-sectional study was carried out among consecutively selected 208 people  with HIV who attended an ART clinic. Memorial Symptoms Assessment Scale (MSAS) was used to  assess the symptoms. Data were collected through the interview method. Descriptive (Mean, SD),  independent t-test, and one-way ANOVA were used for data analysis. Results: Among 208 respondents, the most prevalent symptoms in people with HIV receiving ART  were numbness and tingling sensation in hands and feet (37.5%), followed by lack of energy (33.7%),  pain (29.8%) and weight loss (25.5%). Likewise, the most distressing symptoms were: numbness and  tingling sensation in hands and feet (20.2%), lack of energy (19.8%), pain (18.3%), and feeling sad  (4.3%). Total symptoms score and physical symptoms occurrence were significantly different according  to age, CD4 count, duration of taking ART, and presence of comorbidities. Conclusions: People living with HIV are experiencing various physical and psychological symptoms  despite receiving antiretroviral therapy. These distressing symptoms need to be acknowledged and  managed holistically. Keywords: ART center, Distressing symptoms, Experience, People living with HIV
Keywords: ART center; Distressing symptoms; People living with HIV; Experience